PERISTIWA PERANG MANGGOPOH DI KABUPATEN AGAM SUMATERA BARAT TAHUN 1908 - Shinta Afrima; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Dutch government established a belasting system and got resistance from Minangkabau people. One of the areas that carried out the resistance was Manggopoh resident, Agam Regency, West Sumatra. The purpose of this research is the form of struggle of people of Manggopoh in opposing the belasting system. (a) to find out the cause of Manggopoh war in 1908. (b) to tell the chronology of Manggopoh war in 1908. (c) to find out the tactics used by Manggopoh people against the Dutch colonialists in Manggopoh war in 1908. (d) to find out the cause of the end of Manggopoh war in 1908. (e) to find out the consequences caused by the existence of Manggopoh war in 1908. This study uses a historical method consisting of four stages, namely: Heuristics, Source Criticism, Interpretation, and Historiography. The results of the study showed that the application of the 'belasting' system had caused Manggopoh people opposed the Dutch by carrying out resistance to the Netherlands.Key Words: Events, War, June 16, 1908, Manggopoh, Agam Regency